223k views
5 votes
DO NOT DO IT FOR POINTS, OR I WILL REPORT YOU.

Use Elimination to solve...

5x + 3y = 16
3x – 5y = –4

User Zanko
by
5.8k points

1 Answer

4 votes
Equation 1) 5x + 3y = 16
Equation 2) 3x - 5y = -4

Multiply all of equation 1 by 3, and all of equation 2 by 5.

1) 3(5x+3y=16)

2) 5(3x-5y=-4)

Simplify.

1) 15x + 9y = 48

2) 15x - 25y = -20

Subtract equations from each other.

34y = 68

Divide both sides by 34.

y = 2

Plug in 2 for y in first equation.

5x + 3y = 16

5x + 3(2) = 16

Simplify.

5x + 6 = 16

Subtract 6 from both sides.

5x = 10

Divide both sides by 5.

x = 2

(2, 2)

~Hope I helped!~
User Tempestas Ludi
by
5.7k points